Worldwide Effects of Coronavirus Disease Pandemic on Tuberculosis Services, January–April 2020 - Migliori, Giovanni Battista; Thong, Pei Min; Akkerman, Onno; Alffenaar, Jan-Willem; Álvarez-Navascués, Fernando; Assao-Neino, Mourtala Mohamed; Bernard, Pascale Valérie; Biala, Joshua Sorba; Blanc, François-Xavier; Bogorodskaya, Elena M.; Borisov, Sergey; Buonsenso, Danilo; et al. (Emerging infectious diseases, 2020)
Coronavirus disease has disrupted tuberculosis services globally. Data from 33 centers in 16 countries on 5 continents showed that attendance at tuberculosis centers was lower during the first 4 months of the pandemic in 2020 than for the same period in 2019. Resources are needed to ensure tuberculosis care continuity during the pandemic.